The Function and Roles of ADAMTS-7 in Inflammatory Diseases - Yuying Zhang; Jiqiang Lin; Fanhua Wei (Hindawi Limited, 2015)
The ADAMTS proteinases are a group of multidomain and secreted metalloproteinases containing the thrombospondin motifs. ADAMTS-7 is a member of ADAMTS family and plays a crucial role in the pathogenesis of arthritis. Overexpression of ADAMTS-7 gene promotes the breakdown of cartilage oligomeric matrix protein (COMP) matrix and accelerates the progression of both surgically induced osteoarthritis and collagen-induced arthritis. Moreover, ADAMTS-7 and tumor necrosis factor-α (TNF-α) form a positive feedback loop in osteoarthritis. More significantly, granulin-epithelin precursor, a growth factor has important roles in bone development and bone-associated diseases, disturbs the interaction between ADAMTS-7 and COMP, and prevents COMP degradation. This review is based on our results and provides an overview of current knowledge of ADAMTS-7, including its structure, function, gene regulation, and inflammatory diseases involvement.